'Distinctiveness' and programme diversity in public broadcasting revisited: A seven-country comparison. (1st September 2019) - Hendrickx, Jonathan; Raats, Tim; Ranaivoson, Heritiana; Opgenhaffen, Michaël
AbstractIn the past decade, public service broadcasters have been confronted with major shifts affecting their remit, portfolio and financing. Heavily fuelled by cutbacks and increasing competition, discussions on 'distinctiveness' have resurfaced again and stand central in many policy discussions on the legitimacy of public service broadcasting. This article critically contextualizes discussions on distinctiveness within broader scholarly work on genre and genre diversity in public service broadcasting. It presents the findings of a comparative, quantitative study of the programming schedule of seven public broadcasters (Flanders, Finland, Germany, Hungary, Iceland, Portugal and the United Kingdom). The article addresses how discussions on distinctiveness tap into broader discussions on genre diversity and the amount of entertainment in public service broadcasting programming, how we can assess and compare the diversity of genre programming across different broadcasters, and to what extent high levels of specific genres such as entertainment can be linked to other performance indicators of the selected public broadcasters. The article provides a consistent comparison of genre outputs, based on an original database made of a large set of countries and a high, representative number of programmes and applies a consistent set of indexes to assess not only the share of entertainment but also the diversity of the programming. The underlying question to this article is to what extent genre is still valuable to measure performance and legitimacy of public service broadcasting, considering difficulties of measuring 'genre' as proxy for public service media's (PSM) effectiveness.